2014
DOI: 10.1080/14786451.2014.905578
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the occupants’ behaviour in a university building during winter and summer time

Abstract: The paper focuses on the assessment of indoor comfort and energy consumption of a university building in Cyprus, during winter and summer of 2012 and 2013. The aim was to make a comparative study of the occupants' behaviour and its effects on the building's energy consumption, along with the indoor thermal and visual comfort between the two seasons. American Society of Heating, Refrigerating and Air conditioning Standards are used through a questionnaire campaign and the thermal comfort of occupants is analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Results indicate that during most of the year, users are in thermal comfort without using air-conditioning [223]. Serghides et al [224] identified the inappropriate use of cooling and heating systems (very low temperatures in summer and very high temperatures in winter) in a university building in Cyprus. In the field study carried out in buildings of a university in Malaysia, the results of measurements and questionnaires showed that most of the buildings failed to provide a thermally comfortable environment and that the HVAC system should be changed [8].…”
Section: Thermal Comfort In Universitiesmentioning
confidence: 96%
“…Results indicate that during most of the year, users are in thermal comfort without using air-conditioning [223]. Serghides et al [224] identified the inappropriate use of cooling and heating systems (very low temperatures in summer and very high temperatures in winter) in a university building in Cyprus. In the field study carried out in buildings of a university in Malaysia, the results of measurements and questionnaires showed that most of the buildings failed to provide a thermally comfortable environment and that the HVAC system should be changed [8].…”
Section: Thermal Comfort In Universitiesmentioning
confidence: 96%
“…Azar and Ansari [29] summarized that "contextual factors, which include the ability of occupants to perform a particular action such as changing thermostat set point temperatures, can partially explain why motivation/intent to save energy did not necessarily translate into actions" (Azar and Ansari [29], p. 571). Serghides et al [45] paid particular attention to the equipment, stating that the "number of equipment in use turned out to be one of the most important variables, determining energy consumption" (Serghides et al [45], p. 548), however occupant's intervention on temperature control also affects energy consumption. Lourenço et al [43] analyzed the need to improve energy use management in schools in addition to the building's design and systems.…”
Section: Contextual Determinantsmentioning
confidence: 99%
“…Azar and Ansari [29] collected data from students, faculty, researchers, and staff. Serghides et al [45] collected data from occupants of university buildings, Lourenço et al [43] selected eight secondary schools for their study, and Tornelli [44] researched schools, looking at existing equipment, new construction designs, and behavioral modifications.…”
Section: Contextual Determinantsmentioning
confidence: 99%
“…Figure 7 depicts the chronological evolution of the main milestones reviewed in this investigation, as well as the impacted energy uses in a building. affects occupant behaviour and energy use [94,96,97]; energy-related occupant behaviour surveys [98,99]; etc. Finally, Hong et al [13] discussed the ten main questions affecting occupant behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…They underlined the recommendation of a deeper understanding and interconnection in these fields. Other authors developed studies not only to deepen the knowledge but also to develop new research studies in order to support the different subtasks that are defined by the IEA, represented in Table 2, of the predictability of presence and movement of occupant in buildings [89][90][91]; window opening behaviour in the residential sector [92][93][94] and light switching action [95]; indoor comfort and how it affects occupant behaviour and energy use [94,96,97]; energy-related occupant behaviour surveys [98,99]; etc.…”
Section: Recent Researchmentioning
confidence: 99%